UNDERSTANDING OF ABSTRACT CONCEPTIONS IN THE UNIT OF CELL DIVISION AND HEREDITY THROUGH CONCEPTUAL METAPHORS - Hatice Gülmez GÜNGÖRMEZ (Fırat University, 2019)
The purpose of the present study was to examine eighth grade students’ meta-phorical perceptions in relation to certain conceptions in the specific context of cell division and heredity. The study reflects on the analysis of conceptual metaphors by phenomenological method. The working group of the study was comprised of 20 eight-grade students enrolled in a state school located in the province of Adıyaman. Students participated in the study were presented a form consisting of such questions “chromosome, gene, phenotype, crossing-over and mitosis is as……because….” and asked to fill in the blanks given in the questions. Data collected by the forms were given in descriptives and percentages. In conclusion, 51 metaphors related to 5 distinct conceptions were explored in the analysis. These metaphors were categorized into 4 categories labelled as “living being”, “characteristics/thought/abstract”, “instrument/object” and “course/action”. It was also observed that the most referred category was “characteristics/thought/abstract” generating totally 36 metaphors while the most referred metaphor was “barter” associated with the conception of crossing-over. Most of the students were unable to put in the correct order of DNA, chromosome and gene by size. Considering all these results, it might be suggested that the incompetency of understanding abstract, complex and theoretical phenomena should be challenged by constructive activities improving metaphorical thinking in science courses.